Alessandro Moretta and Transporter Associated With Antigen Processing (TAP) Deficiency: On Giant's Shoulders - Zimmer, Jacques (Frontiers in Immunology, 2019)
The laboratory hosting me for my Ph.D. described in 1994 the first human cases of TAP deficiency in two siblings with recurrent bacterial airway infections and a negative Human Leukocyte Antigen class I (HLA) serotyping. At this time, it became clear that natural killer (NK) cells interact with HLA class I molecules which inhibit them. Inhibitory receptors were postulated, and Alessandro Moretta was the first to generate monoclonal anti-human NK cell antibodies that bound to such molecules, which he characterized in detail (Killer Immunoglobulin-like receptors—KIR). Natural killer cells from healthy donors preferentially kill targets with absent HLA class I molecules (“missing self” concept), whereas we observed that the NK cells from the TAP-deficient patients were hypo-responsive and did not lyse the HLA class I-negative leukemia cell line K562. Moreover, they were not very active in antibody-dependent cellular cytotoxicity assays. To address the question if such NK cells would express KIR or not, my thesis supervisor requested the anti-KIR antibodies from Alessandro Moretta, who was kind enough to provide us generously with aliquots. It turned out that the NK cells from the TAP-deficient individuals expressed most of these inhibitory receptors normally. We then had the privilege to receive almost every new antibody generated in the Moretta lab and to complete the phenotypic studies of the NK cells from our patients. I had the great chance to meet Alessandro Moretta at several occasions. He deeply impressed me each time and strongly influenced my way of thinking.